Detection of adulterations with different grains in wheat products based on the hyperspectral image technique: The specific cases of flour and bread. (April 2016) - Verdú, Samuel; Vásquez, Francisco; Grau, Raúl; Ivorra, Eugenio; Sánchez, Antonio J.; Barat, José M.
Abstract: The objective of this study was to test the capability of a SW-NIR hyperspectral image technique to detect adulterations in wheat flour and bread with cheap grains, such us sorghum, oats and corn, and to compare the hyperspectral information with the physicochemical alterations in the properties of products. Wheat flour was adulterated at four different degrees (2.5, 5, 7.5 and 10%) with sorghum, oat and corn flours. Flours were prepared and used to make bread. Flours and breads were characterized according to several physicochemical parameters (pasting properties, water activity, mass loss during the baking process and texture profile analysis). Crumbs were extracted from breads and conditioned. Hyperspectral image captures were taken of both flours and conditioned crumbs. The data analysis was based on multivariate statistical process control method (MSPC), where the differentiation of adulterated samples was observed in all cases for both flours and crumbs. Finally, in order to relate the image analysis results and the adulterated sample properties, a correlation significance map was created between the physicochemical properties of samples and the multivariate statistical parameters. The SW-NIR image technique was capable of detecting adulterations in each case and high correlation significances were observed (α = 0.01) between wavelengths from specific spectra zones and the physicochemical properties of samples. Highlights: Wheat flour was adulterated by sorghum, oats and corn flour in four percentages. Breads were produced from these adulterated flours. Reflectance spectra of flours and bread crumbs were obtained by imaging technique. Detection of adulterated samples was noted from spectral data on flour and crumb. Relations between changes in flours and crumbs properties and spectrum were observed.